Exploring Variability of Trichodesmium Photophysiology Using Multi-Excitation Wavelength Fast Repetition Rate Fluorometry - Zhu, Yuanli; Feng, Yuanyuan; Browning, Thomas J.; Wen, Zuozhu; Hughes, David J.; Hao, Qiang; Zhang, Ruifeng; Meng, Qicheng; Wells, Mark L.; Jiang, Zhibing; Dissanayake, P. A. K. N.; Priyadarshani, W. N. C.; et al. (Frontiers in Microbiology, 2022)
Fast repetition rate fluorometry (FRRf) allows for rapid non-destructive assessment of phytoplankton photophysiology in situ yet has rarely been applied to Trichodesmium. This gap reflects long-standing concerns that Trichodesmium (and other cyanobacteria) contain pigments that are less effective at absorbing blue light which is often used as the sole excitation source in FRR fluorometers – potentially leading to underestimation of key fluorescence parameters. In this study we use a multi-excitation FRR fluorometer (equipped with blue, green and orange LEDs) to investigate photophysiological variability in Trichodesmium assemblages from two sites. Using a multi-LED measurement protocol (447+519+634 nm combined) we assessed maximum photochemical efficiency (F_v/F_m), functional absorption cross section of PSII (σ_PSII), and electron transport rates (ETR) for natural Trichodesmium assemblages in both the Northwest Pacific (NWP) and North Indian Ocean in the vicinity of Sri Lanka (NIO-SL). Evaluating fluorometer performance, we showed that use of a multiple-LED measuring protocol yields a significant increase of F_v/F_m for Trichodesmium compared to using blue-only excitation. We found distinct photophysiological differences for Trichodesmium at both locations with higher average F_v/F_m as well as lower σ_PSII and nonphotochemical quenching (〖NPQ〗_NSV) observed at NWP compared to NIO-SL (Kruskal-Wallis t-test df=1, p < 0.05). Fluorescence light response curves (FLC) further revealed differences in electron transport rate (ETR) response with a lower initial slope (α_ETR) and higher maximum electron turnover rate (〖ETR〗_PSII^max) observed for Trichodesmium at NWP compared to NIO-SL, translating to a higher averaged light saturation E_K (=〖ETR〗_PSII^max/α_ETR) for cells at this location. Spatial variations in physiological parameters were both observed between and within regions, likely linked to nutrient supply and physiological stress. Finally, we apply an algorithm to estimate primary productivity of Trichodesmium using FRRf-derived fluorescence parameters, yielding an estimated carbon-fixation rate ranging from 0.35 to 49 mgC mg Chl-a−1 h−1 across this dataset. Overall, our findings demonstrate that the capacity of multi-excitation FRRf to advance the application of Chl-a fluorescence techniques in phytoplankton assemblages of cyanobacteria, and reveals novel insight into environmental regulation of photoacclimation in natural Trichodesmium populations.